Alterations of the paired maternal vaginal microbiome and neonatal meconium microbiome in vulvovaginal candidiasis positive pregnant women - Zhang, Hongqin; Li, Hongping; Zhang, Ruolin; Ji, Lingxia; Chen, Jun; Nie, Chuan; Huang, Weimin (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundWomen with vulvovaginal candidiasis (VVC) are known to experience vaginal microbial dysbiosis. However, the dynamic alterations of the vaginal microbiome in pregnant women with VVC and its effect on neonatal gut microbiome remain unclear. This study aims to characterize the vaginal microbiome in pregnant women with VVC and its impact on their offspring’s meconium microbiome.MethodsForty-four pregnant women, including 17 with VVC (VVC group) and 27 healthy controls (HC group), along with their 44 offspring, were enrolled in this study. Maternal vaginal samples were collected during the pre- and post-delivery phases. Meconium samples from their newborns were also obtained. Microbial communities were characterized using 16S rRNA sequencing.ResultsThe vaginal microbiome of healthy pregnant women was predominantly composed of the genus Lactobacillus. The Bray-Curtis dissimilarity index indicated significant alterations in the vaginal microbiome of the VVC group, with a notable decrease in Lactobacillus and significant increases in Delftia, Burkholderia during both the pre- and post-delivery phases compared to the HC group. Additionally, the neonatal meconium microbiome exhibited significant differences between the VVC and HC groups, with L. salivarius and L. helveticus significantly decreased and Delftia significantly increased in the VVC group. Similar trends in microbial variation were observed across maternal and neonatal microbiomes, indicating intergenerational concordance associated with VVC.ConclusionVVC alters the microbiota of both pregnant women and their neonates at birth, suggesting a form of microbial inheritance. These findings underscore the distinctive characteristics of the vaginal microbiome associated with VVC and its potential impact on the formation of early-life gut microbiome.